KEWAJIBAN ANAK TERHADAP ORANG TUA: (TINJAUAN TAFSIR AL-MARAGHI SURAT AL-AHQAF AYAT 15-20) - Idris, M. Arif; Putriani, Putriani (AT-TA'DIB: JURNAL ILMIAH PRODI PENDIDIKAN AGAMA ISLAM, 2024)
This study analyzes the obligations of children to both parents based on Al-Maraghi's interpretation of Surah Al-Ahqaf verses 15-20. The results of the study show that children have two primary obligations. First, doing good to parents includes loving, cherishing, respecting, and obeying their commands as long as they do not contradict the sharia. This obligation also includes responding to their calls immediately, being friendly, putting their interests first, maintaining relationships, sacrificing for them, and providing for themselves. Tafsir Al-Maraghi emphasizes the importance of love and devotion to both parents during their lifetime. Second, pray for the good of both parents, both living and deceased. Prayer becomes a form of devotion not limited by time, reflecting deep respect and affection. This study affirms the relevance of Islamic values in the relationship between children and parents, which is emphasized in Al-Maraghi's tafsir as an ethical and spiritual foundation for building a harmonious and blessed family.